Agricultural insurances based on meteorological indices: realizations, methods and research agenda - Antoine Leblois; Philippe Quirion (Fondazione Eni Enrico Mattei (FEEM), 2010)
In many low-income countries, agriculture is mostly rainfed and yields highly depend on climatic factors. Furthermore, farmers have little access to traditional crop insurance, which suffers from high information asymmetry and transaction costs. Insurances based on meteorological indices could fill this gap since they do not face such drawbacks. However their implementation has been slow so far. In this article, we first describe the most advanced projects that have taken place in developing countries using these types of crop insurances. We then describe the methodology that has been used to design such projects, in order to choose the meteorological index, the indemnity schedule and the insurance premium. We finally draw an agenda for research in economics on this topic. In particular, more research is needed on implementation issues, on the assessment of benefits, on the way to deal with climate change, on the spatial variability of weather and on the interactions with other hedging methods.
Keywords: G21; O12; Q12; Q18; Q54; 330; Agriculture; Insurance; Climatic Risk